The Aesthetics Effect of Surakarta-Style Pakeliran on East Javanese Pakeliran - Nugroho, Sugeng (Harmonia: Journal of Arts Research and Education, 2018)
This study intends to explore the aesthetics of East Javanese Shadow Puppet (Wayang Kulit Jawa Timuran) show as one of the peopleÃ¢â‚¬â„¢s style puppet show model. The problems discussed are related to how East Javanese Shadow Puppeteers respond to the existence of The Surakarta-style shadow puppet shows that are not only flourished in the Central Java region but also in most parts of East Java. This study uses qualitative methods with descriptive analytical analysis. Research data are collected through literature studies, documentation studies, interviews, and field observations. The results of the study show that East Javanese shadow puppet show, both performance elements, the structure, and some elements of Ã¢â‚¬Å“garap pakeliranÃ¢â‚¬Â have currently been colored by the idioms of Surakarta-style shadow puppet show.